Improving Patient Rehabilitation Performance In Exercise Games Using Collaborative Filtering Approach - Waidah Ismail; Ismail Ahmed Al-Qasem Al-Hadi; Crina Grosan; Rimuljo Hendradi (Peer J Computer Science, 2024)
Indexed by WOS/Scopus/ERA